2014
DOI: 10.7314/apjcp.2014.15.20.8607
|View full text |Cite
|
Sign up to set email alerts
|

Association between Socioeconomic Status and Altered Appearance Distress, Body Image, and Quality of Life Among Breast Cancer Patients

Abstract: Background: Breast cancer patients experience a variety of altered appearance -such as loss or disfigurement of breasts, discolored skin, and hair loss -which result in psychological distress that affect their quality of life. This study aims to evaluate the impact of socioeconomic status on the altered appearance distress, body image, and quality of life among Korean breast cancer patients. Materials and Methods: A cross-sectional survey was conducted at advocacy events held at 16 different hospitals in Korea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
2
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 26 publications
5
67
2
11
Order By: Relevance
“…Moderate to high levels of fear associated with concerns of disease recurrence were noted in 56% of Dutch BC survivors (Deimling et al, 2006). Other studies have focussed on particular predictive factors for PTSD, including effects of negative stressors like young age at diagnosis (Andrykowski et al, 2000;Andrykowski et al, 1998), lower socio economic status (Cordova et al, 2001), low educational achievement (Cordova et al, 2001;Chang et al, 2014), emotional social environment (Tjemsland et al, 1998), poor social support and reduced physical activity (Smith et al, 2008). The above mentioned factors are commonly predictive of PTSD after BC diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moderate to high levels of fear associated with concerns of disease recurrence were noted in 56% of Dutch BC survivors (Deimling et al, 2006). Other studies have focussed on particular predictive factors for PTSD, including effects of negative stressors like young age at diagnosis (Andrykowski et al, 2000;Andrykowski et al, 1998), lower socio economic status (Cordova et al, 2001), low educational achievement (Cordova et al, 2001;Chang et al, 2014), emotional social environment (Tjemsland et al, 1998), poor social support and reduced physical activity (Smith et al, 2008). The above mentioned factors are commonly predictive of PTSD after BC diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Bellizzi argues that the perceived ongoing threat of BC recurrence leads to long term stress and can develop into chronic psychological conditions (Bellizzi et al, 2010). Chang and colleagues in their research found that altered appearance such as loss or disfigurement of breasts, discoloured skin, and hair loss results in psychological distress and affects their quality of life (Chang et al, 2014). Another report indicated that psychosocial distress experienced within the first year post diagnosis has a huge impact on psychosocial wellbeing and quality of life in long term BC survivors (Mehnert and Koch, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important determinant of the ability of breast cancer patients to cope with their illness and treatments is the perceived social support (PSS), which can be defined as the extent to which an individual believes that his/her needs for support, information and feedback are fulfilled [15]. The perceived availability of interpersonal resources, such as the verbal and nonverbal communication of caring and concern, including listening, ‘being there', emphasizing, reassuring and comforting [16], can protect persons from potentially adverse effects of stressful events (buffering model) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, emotional well-being is affected and this disruption in the normal psychological function is related to the alterations in the body image (Anillo, 2000;Avis, Crawford & Manuel, 2004;Begovic-Juhant, Chmielewski , Iwuagwu & Chapman , 2012;Brandberg et al, 2008;Chang et al, 2014;Collins et al, 2011;Falk, Reinertsen, Nesvold, Fossa & Dahl, 2010;Fobair et al, 2006;Helms, O'Hea & Corso, 2008;. McClelland, Holland & Griggs, 2015;Przezdciecki et al, 2013).…”
mentioning
confidence: 99%